Monitoring the risks of infections associated with medical care in a hospital in Rostov-on-Don - Mrs Kristina Markova; Mrs Elena Goloshva; Mrs Anna Aleshukina; Mrs Inna Polishchuk; Mrs Iraida Berezinskaya; Mrs Larisa Ermakova; Ms Vadim Melnik (International Journal of Infectious Diseases)
Introduction: One of the comprehensive measures to prevent cases of healthcare-associated infections (HAI) in hospitals is a modern science-based approach to monitoring the circulation of opportunistic antibiotic-resistant microorganisms in medical organizations. Methods: During 2022 -2023 158 samples were taken from the oropharynx of medical staff. 64 samples from the skin of the hands of medical personnel and 132 swabs from inventory and equipment in hospital departments. We investigated intensive care unit (injection pillow, ventilation grille); surgical department (treatment room: central heating radiator, couch, table for manipulations; dressing room: couch, cabinet for sterile material; ward: refrigerator, fluorescent lamp); geriatric department: couch; treatment room: split system, tourniquet; registration desk at the nurse's station, doctors' desks)were examined Differential diagnostic media were used to isolate microorganisms. Isolates were identified by mass spectrometry using the MALDI-TOFF method (Byotyper Microflex, Bruker Germany). The main criterion for the risk of HAI was the determination of antibiotic resistance in isolated cultures, tested by the disk diffusion method. Results: An examination of the hospital inventory showed that gram-positive microorganisms dominated, including staphylococci in 58% of cases. Non-fermentative gram-negative bacteria (NFB) (A. lwoffii, S. maltophilia, P. montelii) were detected in 9% of cases.In 2023, there was an increase in the number of sterile sampling points from hospital facilities.The dominant microorganisms in the oropharynx of employees during the study periods were: Staphylococcus spp. (29%), Streptococcus spp. (19%), Candida spp. (11%), NGOB (7%). Compared to 2022, in 2023, the content of bacteria of the family Enterobacteriacae and Neisseria spp. in the oropharynx of employees decreased, against the background of an increase in the content of Streptococcus spp., pathogenic S. aureus and hemolyzing S. epidermidis.Among the microorganisms isolated from the hands of hospital employees, the dominant species were: Staphylococcus spp. (71%), E.coli (11%), Lactobacillus spp. (6%), Candida spp. (2%), as well as mold fungi (2%). Discussion: The results obtained may indicate an increase in the risk of HAI in this hospital associated with potentially pathogenic and pathogenic representatives of their own microflora circulating among employees.The analysis of antibiograms of microorganism strains isolated from the hands of personnel and from hospital inventory showed increase in the degree of resistance of isolates in relation to antibiotics of later generations (fluoroquinolones, aminoglycosides of the second generation, cephalosporins of the third generation, semisynthetic penicillins of the second generation, macrolides). Conclusion: Changes in the species composition and sensitivity to antibiotics of microflora isolated from medical personnel and microflora from hospital facilities and equipment suggest the presence of an epidemiological connection that increases the risk of developing HAI in this hospital.